Global and Malaysian aromatic rice: a comparative review on the quality, production, and breeding spectra - Aliif Ihsaan Akmal Shukri; Shamsiah Abdullah; Nur Suraya Abdullah; Sobri Hussein; Noorshilawati Abdul Aziz; Mohd Shahril Firdaus Ab Razak; Faiz Ahmad; Nor 'Aishah Hasan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Aromatic rice is a premium rice variety due to multiple distinctive essential qualities viz., strong aroma, long grain, intermediate amylose content, and intermediate gelatinization temperature. The strong aroma is majorly contributed by 2-acetyl-1-pyrroline (2AP), a volatile organic compound that is 10-100% higher in aromatic rice. The long grain represents a large endosperm that contains more starch and nutrients. Intermediate amylose content in aromatic rice is preferred as the rice becomes moist and tender upon cooking. As for the gelatinization temperature (GT), aromatic rice has an intermediate GT which defines a shorter time in cooking. In the world, major aromatic rice cultivars include Basmati (India & Pakistan) and Khao Dawk Mali 105 (Thailand). The production of the aforementioned varieties as well as other minorities is declining due to multiple constraints. The demand-export clash, climate change, disease outbreaks, and other abiotic factors have proven challenging for all rice industrial players. Several breeding techniques are practiced in combatting those problems. In the past, conventional pure line breeding had proven to initiate the cultivation of Basmati-370 (India) and Khao Dawk Mali 105 (Thailand). However, hybrid breeding (combination of desirable traits) is a much more effective breeding method through the release of Pusa Basmati-1 (India), Lateefy (Pakistan), and MRQ104 (Malaysia). From the genetic perspective, quantitative traits locus (QTL) mapping is used to assist in the breeding of aromatic rice cultivars. QTL mapping successfully improved yield, agronomic traits, and stress resistance by providing a strong foundation for advanced in-depth breeding technologies including marker-assisted selection (MAS), mutagenesis, and CRISPR/Cas9 mediated genome editing.